2022
DOI: 10.1002/csr.2364
|View full text |Cite
|
Sign up to set email alerts
|

Walking the talk, but above all, talking the walk: Looking green for market stakeholder engagement

Abstract: In recent years, corporate environmental commitment is showing different postures going from greenwashing to undue modesty and from environmental excellence to environmental inaction. In this paper, we go a step beyond the most recent research work on the dichotomy greenwashing-brownwashing and develop a more comprehensive model that reflect more subtly four main corporate environmental strategic positions based on both firm's environmental performance and disclosure achievements. Jointly with their characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 85 publications
(178 reference statements)
0
1
0
Order By: Relevance
“…This outperformance is stronger in sectors where firms rely heavily on the extraction of large amounts of natural resources (Eccles et al, 2011), such as utilities. Previous research has also concluded that companies' environmental communication can be rewarded with better performance in financial markets (Amores-Salvad o et al, 2022). Although there are several studies focused on the impact of a company's ESG policy on its economic and financial performance (Abdelmotaal & Abdel-Kader, 2016;Hussain et al, 2018), there is hardly any study focused on the utilities industry considering the stock returns as a measure of market-based financial performance.…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%
“…This outperformance is stronger in sectors where firms rely heavily on the extraction of large amounts of natural resources (Eccles et al, 2011), such as utilities. Previous research has also concluded that companies' environmental communication can be rewarded with better performance in financial markets (Amores-Salvad o et al, 2022). Although there are several studies focused on the impact of a company's ESG policy on its economic and financial performance (Abdelmotaal & Abdel-Kader, 2016;Hussain et al, 2018), there is hardly any study focused on the utilities industry considering the stock returns as a measure of market-based financial performance.…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%